Extrinsic Compression of the Gastric Wall by a Ventriculoperitoneal Shunt Catheter: Case Report and Literature Review - Alencar, Guilherme dos Santos de; Trindade, Érico Samuel Gomes Galvão da; Sarquis, Lucas Mansano; Foltran, Rodrigo Stremel; Jaouhari, Eduardo Talib Bacchi; Borba, Luis Alencar Biurrum (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Ventriculoperitoneal (VP) shunt is commonly used in the treatment of hydrocephalus and may present complications in up to 30% of patients. The present report addresses an uncommon complication in the abdominal cavity, in which the catheter caused extrinsic compression of the gastric wall.Case report A 30-year-old man presented a decreased level of consciousness, associated with severe headache and vomiting. He had a history of congenital neurotoxoplasmosis and VP shunt insertion at 7 years of age. Imaging exams demonstrated the formation of an encapsulated retrogastric pseudocyst and extrinsic compression of the gastric wall by a VP shunt catheter. Through videolaparoscopy, decompression of the gastric wall and removal of the pseudocyst were performed, with the reestablishment of the drainage of cerebrospinal fluid. An analysis of the distal fragment of the removed catheter revealed obstruction by fibrotic material. The patient was discharged with a reestablished baseline after four days of hospitalization.Comments The literature shows that ∼ 47% of the complications presented by patients are related to the distal end of the catheter, and 8.2% of these come from migration to the abdominal cavity. However, there is an extreme paucity of studies that demonstrate extrinsic compression of the gastric wall by a VP shunt catheter. Therefore, we suggest that further studies on complications involving the VP shunt be performed to improve diagnostic and therapeutic results, in addition to complementing the literature on this complication.
Keywords: hydrocephalus; ventriculoperitoneal shunt; complications; extrinsic compression; gastric wall